Heat transfer mechanism in idealized healthy and diseased aortas using fluid-structure interaction method - Qiao, Yonghui; Luo, Kun; Fan, Jianren (Biomechanics and modeling in mechanobiology, 2023)
The heat transfer mechanism inside the human aorta may be related to the physiological function and lesion formation of the aortic wall. The objective of this study was to acquire the temperature distribution in the three-dimensional idealized aorta. An idealized healthy aortic geometry and three representative diseased aortas: aortic aneurysm, coarctation of the aorta, and aortic dissection were constructed. Advanced fluid-structure interaction (FSI) computational framework was applied to predict the aortic temperature distribution. The movement of the aortic root due to the heartbeat was also considered. The displacement distribution of the aortic vessel wall was consistent with clinical observation. The lesser curvature of the aortic arch, aneurysm body, coarctation region, and false lumen were all exposed to relatively high temperatures (over 310.006 K). We found that the rigid wall assumption slightly underestimated the magnitude of the whole aortic wall-averaged temperature while the changing trend and local temperature were like the results of the FSI method. Besides, the wall-averaged temperature would increase and the temperature inflection point would advance when the aortic vessel wall was loaded with a high heat flux. This pilot study revealed the aortic heat transfer mechanism and temperature distribution, and the findings may help to understand the physiological characteristics of the aortic vessel wall.